2015
DOI: 10.1002/bies.201500017
|View full text |Cite
|
Sign up to set email alerts
|

Modification of pro‐inflammatory signaling by dietary components: The plasma membrane as a target

Abstract: You are what you eat - this well-known phrase properly describes the phenomenon of the effects of diet on acute and chronic inflammation. Several lipids and lipophilic compounds that are delivered with food or are produced in situ in pathological conditions exert immunomodulatory activity due to their interactions with the plasma membrane. This group of compounds includes cholesterol and its oxidized derivatives, fatty acids, α-tocopherol, and polyphenols. Despite their structural heterogeneity, all these comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 123 publications
0
13
0
Order By: Relevance
“…It has been suggested that some of the anti-inflammatory effects of tocopherol are independent of its antioxidant activity [44]. Plasma membrane lipid rafts containing tocopherol can interact with TLRs and may be important in the response to LPS exposure and sepsis [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that some of the anti-inflammatory effects of tocopherol are independent of its antioxidant activity [44]. Plasma membrane lipid rafts containing tocopherol can interact with TLRs and may be important in the response to LPS exposure and sepsis [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…This could also be valid for the animals used as a model of study. Furthermore, as mentioned above, the TLR-4 function and expression are modulated not only by genetic variants and haplotypes [11,85,86] but also by environmental factors (such as diet [138][139][140][141], mite allergens [142], air pollution [143]), and their cross-interaction with microbiota [141], which may remain in a healthy state or show alterations (i.e. dysbiosis and consequent endotoxemia associated with age or obesity) [144,145]and consequent epigenetic changes [146,147].…”
Section: Therapeutic Role Of Tlr-4 Pathway: From Experimental Data Tomentioning
confidence: 99%
“…These data show the influence of dietary lipids on the inflammatory reactions of the organism providing a rationale for pro-health changes in dietary habits. They also justify the interest in the molecular mechanisms of the pro-and anti-inflammatory properties of dietary components, as we discussed in [30,31].…”
Section: Lipids As Modulators Of Lps-induced Signalingmentioning
confidence: 76%